Facile Total Synthesis of Thailandepsins D–F: Novel Bicyclic Depsipeptide Histone Deacetylase Inhibitors Isolated from a Microorganism - Sayar, Noel; Narita, Koichi; Katoh, Tadashi (Synthesis, 2019)
The naturally occurring bicyclic depsipeptide histone deacetylase inhibitors thailandepsins D–F were efficiently synthesized for the first time in 49–61% overall yield over five steps, starting from known amine and carboxylic acid segments. The synthesis includes the condensation of the two known starting materials to directly assemble the corresponding seco-acids, which are the key precursors for macrolactonization. The seco-acids are then macrolactonized using the Shiina method to construct the requisite 15-member macrocycles.
Keywords: thailandepsin; histone deacetylase inhibitor; natural products; bicyclic depsipeptide; total synthesis; macrocycles